Parents preference and willingness to pay for private senior high school education - Rosali, Leann Jester; Debildos, Jennelyn; Gatmaitan, Eric (Journal of Management and Business Education, 2024)
This descriptive research investigates the parents’ preferences when selecting a school for their children and their willingness to pay for a private senior high school education in South Cotabato, Philippines. This study focuses on the preferences influencing parents' decisions to choose private education within the distinct socio-economic context of the research locale. Primary household data were gathered through a survey targeting parents of junior high school students. The study reveals that the predominant demographic seeking private senior high school education in the research setting are clients belonging to the low to upper-middle-income bracket. While these parents prioritize investing in quality education, their spending flexibility is constrained. Consequently, their willingness to pay for a private senior high school education and their school choices are significantly shaped by their income levels, perceptions of an acceptable price point, and the availability of government subsidies. This investigation yields valuable insights into the educational market dynamics which are essential for enhancing the sustainability of private education in the Philippines.